Clinical features and power spectral entropy of electroencephalography in Wilson's disease with dystonia. Issue 12 (25th October 2022) - Zhang, Shaoru; Liu, Aiqun; Zhou, Zhihua; Huang, Zheng; Cheng, Jing; Chen, Danping; Zhong, Qizhi; Yu, Qingyun; Peng, Zhongxing; Hong, Mingfan
Abstract: Objective: To study the clinical features and power spectral entropy (PSE) of electroencephalography signals in Wilson's disease (WD) patients with dystonia. Methods: Several scale evaluations were performed to assess the clinical features of WD patients. Demographic information and electroencephalography signals were obtained in all subjects. Results: 34 WD patients with dystonia were recruited in the case group and 24 patients without dystonia were recruited in the control group. 20 healthy individuals were included in the healthy control group. The mean body mass index (BMI) in the case group was significantly lower than that in the controls ( p < .05). The case group had significantly higher SAS, SDS, and Bucco‐Facial‐Apraxia Assessment scores ( p < .05). Total BADS scores in the case group were lower than those in the control group ( p < .01). Note that 94.11% of the case group presented with dysarthria and 70.59% of them suffered from dysphagia. Dysphagia was mainly related to the oral preparatory stage and oral stage. Mean power spectral entropy (PSE) values in the case group were significantly different ( p < .05) from those in the control group and the healthy group across the different tasks. Conclusions: The patients with dystonia were usually accompanied with low BMI, anxiety, depression, apraxia, executive dysfunction, dysarthria and dysphagia. The cortical activities of the WD patients with dystonia seemed to be more chaotic during the eyes‐closed and reading tasks but lower during the swallowing stages than those in the control group. Abstract : WD patients with dystonia were more susceptible to suffer from low BMI and highߚlevel neurological dysfunctions. It was the first time to apply the PSE of EEG to detect the cortical synaptic activity in WD patients. The cortical activities of the WD patients with dystonia seemed to be more chaotic during the eyes‐closed and reading tasks but lower during the swallowing stages than those in the control group.